Safety and Efficacy of Rituximab in Multiple Sclerosis: A Retrospective Observational Study - Bassem I. Yamout; Nabil K. El-Ayoubi; Johny Nicolas; Yehya El Kouzi; Samia J. Khoury; Maya M. Zeineddine (Journal of Immunology Research)
Objective. To evaluate the efficacy and safety of rituximab in multiple sclerosis in a clinical practice setting. Methods. Clinical data for all adult patients with multiple sclerosis (MS) treated with off-label rituximab at a single MS center in Lebanon between March 2008 and April 2017 were retrospectively collected from medical charts. The main efficacy outcomes assessed were annualized relapse rate (ARR) and proportion of patients free from relapses, disability progression, or magnetic resonance imaging (MRI) activity. Results. A total of 89 rituximab-treated patients were included: 59 relapsing-remitting MS (RRMS) and 30 progressive MS (PMS). Patients were treated with 1000 or 2000 mg rituximab IV every 6–12 months for a mean duration of 22.2 ± 24.8 months. The subjects were 65.2% females with a mean age of 40.5 ± 12.3 years and a mean disease duration of 7.9 ± 6.2 years. During treatment, the ARR decreased from 1.07 at baseline to 0.11 in RRMS (p<0.0001) and from 0.25 to 0.16 in PMS patients (p=0.593). The mean Expanded Disability Status Scale (EDSS) remained unchanged in both RRMS and PMS patients. Between baseline and the last follow-up, the percent of patients free from any new MRI lesions increased from 18.6% to 92.6% in the RRMS group and from 43.3% to 82% in the PMS group. No evidence of disease activity (NEDA) was achieved in 74% of patients at 1 year of treatment. A total of 64 adverse events (AEs) (71.9%) were recorded with the most common being infusion-related reactions in 25.8% of patients, all mild in nature. Two of our rituximab-treated patients experienced serious AEs requiring surgical interventions: pyoderma gangrenosum vaginalis with perianal abscess and fistula and an increase in the size of a meningioma. No case of progressive multifocal leukoencephalopathy (PML) was detected. Conclusion. In our real-world cohort, rituximab was well-tolerated and effective in reducing relapse rate and disability progression in relapsing-remitting and progressive MS patients.